Étude de l’influence des couches de non-tissés intermédiaires dans la réversibilité du doublage thermoplastique au Plextol B500® - Virginie Le Poizat (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Choices about materials and the elaboration of synthetic linings are often made by the conservator, without any precise experimentation. Reversibility is an important deontological principal, not well-known concerning synthetic lining. We studied thanks to experimentations, how it can be influenced by the choice of the intermediate layers.